1994
DOI: 10.1177/004947559402400302
|View full text |Cite
|
Sign up to set email alerts
|

The Reasons for Amputations in Children (0–18 Years) in a Developing Country

Abstract: This study describes 49 young amputees who either have attended or have been operated at the Orthopaedic Department of Dodoma Regional Hospital from 1983 to 1991. Emphasis has been put on the aetiological factors of 56 amputations under review, underlying those that are typical of the Least Developed Countries in Africa and highlighting how they interrelate with the beliefs and traditions of the African society. Apart from 14 amputations performed for trauma of different type, important roles were played by ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Most of our amputations were performed in the lower limbs like other studies (4, 16). This finding is in agreement with earlier findings that lower extremities are injured more often than the upper extremities and diabetic gangrene is common in the lower extremities than elsewhere on the body (3, 24, 25). All of patients with diabetics had lower extremity amputations in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Most of our amputations were performed in the lower limbs like other studies (4, 16). This finding is in agreement with earlier findings that lower extremities are injured more often than the upper extremities and diabetic gangrene is common in the lower extremities than elsewhere on the body (3, 24, 25). All of patients with diabetics had lower extremity amputations in our study.…”
Section: Discussionsupporting
confidence: 93%
“…This finding confirms the earlier findings that lower extremities are injured more often than the upper extremities and diabetic gangrene is common on the lower extremities than elsewhere on the body [5,29,30]. However, other studies reported above knee amputation as the most common procedure performed than below knee amputation [3,18,31].…”
Section: Discussionsupporting
confidence: 89%
“…There is meagre literature about the care of children in hospitals in developing countries. Where it does exist, it usually covers topics such as morbidity and/or mortality of certain diseases (Nakamura 1992; Choudhury et al 1990; Gamatie et al 1994; Loro et al 1994), the use of technology (Basch 1993; Perry & Marx 1992) and services for disabled children (Wallace 1991). Nursing in developing countries has been discussed, usually by nurses from developed countries who visit to teach nursing (Toyoshima 1994; Conrad 1997) or to develop research programmes (Kirkpatrick 1990; Mangay‐Maglacas 1992).…”
Section: Children In Hospital In Developing Countriesmentioning
confidence: 99%